A closer look to cell structural barriers affecting starch digestibility in beans. (1st February 2018) - Rovalino-Córdova, Ana M.; Fogliano, Vincenzo; Capuano, Edoardo
Graphical abstract: Highlights: In beans, the rate of starch hydrolysis decreases with increasing cell intactness. Cell walls that encapsulate starch are permeable to digestive enzymes. Enzymatic modification of cell wall facilitate the access of digestive enzymes. Protein matrix in cell cytoplasm modulates starch digestion. Abstract: Isolated bean cells were used to understand the contribution of cell wall and cytoplasmic matrix on starch digestibility. Cotyledon cells were treated enzymatically and mechanically to reduce the level of cell intactness. SEM and chemical characterization revealed that enzymatic treatment modified cell wall thickness and porosity without altering the cytoplasmic matrix, whereas mechanical treatment completely disrupted cell structure. Decreasing cell intactness increased the rate but not the extent of starch digestion in-vitro . It was concluded that cell wall serves as a permeable barrier limiting the access of digestive enzymes. Cytoplasmic matrix, on the other hand, reduced further the accessibility of amylase to starch affecting its hydrolysis rate. In addition, it was proven that cell structural changes, if any, occurring during digestion had no effect on starch hydrolysis.